Sport Training Technology Based on PsychoEmotional Approach in the Paralympic Sport of Goalball - Palibaeva Zulfiya Khalmakhanovna (Zien Journals, 2023)
In the light of its prospects and significance, it is important to apply an approach based on purposeful, conscious regulation of the psycho-emotional state of athletes in the process of training. The improvement of psychophysical training based on this approach, the development on this basis of a complex of physical culture and sports exercises in the field of adaptive physical culture and Paralympic sports, and its approbation in the training process of goalball players are considered
Keywords: Paralympic sport; goalball; adaptive physical culture and sport; training process